ANALISIS PENDAPATAN USAHATANI ALPUKAT DI KECAMATAN BANDING AGUNG KABUPATEN OGAN KOMERING ULU SELATAN (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2019)
This study aims to analyze the income of avocado farming in Kecamatan Banding Agung, South Ogan Komering Ulu Regency. The method used in this study is the method of Survey to the farmers, namely: avocado farmers in District Banding Agung South Ogan Komering Ulu Regency. The data used in this study consist of primary and secondary data. The results of research that has been done then can be drawn a conclusion that the Avocado Farming in District Appeals Agung Ogan Komering Ulu Regency has an average income of Rp.5.254.992.42 / Year.